Persistent Organochlorine Pesticides and Risk of Testicular Germ Cell Tumors - McGlynn, Katherine A.; Quraishi, Sabah M.; Graubard, Barry I.; Weber, Jean-Philippe; Rubertone, Mark V.; Erickson, Ralph L. (JNCI : Journal of the National Cancer Institute, 2008)
Background Exposure to endocrine-disrupting chemicals, such as persistent organochlorine pesticides, has been suggested to increase the risk of testicular germ cell tumors (TGCTs). Methods To study the relationship of POP exposure to TGCT risk, prediagnostic serum samples from 754 case subjects and 928 control subjects enrolled in the Servicemen’s Testicular Tumor Environmental and Endocrine Determinants Study were analyzed for cis-nonachlor, trans-nonachlor, oxychlordane, total chlordanes, β-hexachlorocyclohexane, mirex, p,p′-dichlorodiphenyldichloroethylene (p,p′-DDE), and p,p′-dichlorodiphenyltrichloroethane. Adjusted odds ratios (ORs) and their associated 95% confidence intervals (CIs) for the risk of TGCT overall and for the histological subgroups, seminoma and nonseminoma, were estimated using multivariable logistic regression. All statistical tests were two-sided. Results TGCT risk was statistically significantly associated with higher plasma levels of p,p′-DDE (for highest quartile [Q4] vs lowest quartile [Q1], OR = 1.71, 95% CI = 1.23 to 2.38, Ptrend = .0002) and of two chlordane components, cis-nonachlor (Q4 vs Q1, OR = 1.56, 95% CI = 1.11 to 2.18, Ptrend = .009) and trans-nonachlor (Q4 vs Q1, OR = 1.46, 95% CI = 1.07 to 2.00, Ptrend = .026). Seminoma risk was statistically significantly associated with p,p′-DDE (Q4 vs Q1, OR = 1.91, 95% CI = 1.22 to 2.99, Ptrend = .0008), cis-nonachlor (Q4 vs Q1, OR = 1.93, 95% CI = 1.27 to 2.93, Ptrend = .0045), trans-nonachlor (Q4 vs Q1, OR = 1.72, 95% CI = 1.11 to 2.67, Ptrend = .033), and a chlordane metabolite, oxychlordane (Q4 vs Q1, OR = 1.64, 95% CI = 1.04 to 2.60, Ptrend = .048), whereas nonseminoma risk showed a statistically significant association with p,p′-DDE only (Q4 vs Q1, OR = 1.63, 95% CI = 1.10 to 2.42, Ptrend = .0044). Conclusions Increased exposure to p,p′-DDE may be associated with the risk of both seminomatous and nonseminomatous TGCTs, whereas exposure to chlordane compounds and metabolites may be associated with the risk of seminoma. Because evidence suggests that TGCT is initiated in very early life, it is possible that exposure to these persistent organic pesticides during fetal life or via breast feeding may increase the risk of TGCT in young men.